2017
DOI: 10.1155/2017/1764523
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Engineering to Repair Diaphragmatic Defect in a Rat Model

Abstract: Tissue engineering is an emerging strategy for repairing damaged tissues or organs. The current study explored using decellularized rat diaphragm scaffolds combined with human amniotic fluid-derived multipotent stromal cells (hAFMSC) to provide a scaffold, stem cell construct that would allow structural barrier function during tissue ingrowth/regeneration. We created an innovative cell infusion system that allowed hAFMSC to embed into scaffolds and then implanted the composite tissues into rats with surgically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 46 publications
0
20
0
Order By: Relevance
“…Mesenchymal stem cell (MSC) treatment is a new regenerative therapy for treating tendon disorders. Preclinical studies have reported that MSC therapy may increase the number of tenocytes and regenerate the injured tendon tissue [1][2][3][4]. While several studies with animals support the treatment of tendon disorders using MSCs, little is known about the efficacy and safety of MSCs to treat these conditions in humans.…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cell (MSC) treatment is a new regenerative therapy for treating tendon disorders. Preclinical studies have reported that MSC therapy may increase the number of tenocytes and regenerate the injured tendon tissue [1][2][3][4]. While several studies with animals support the treatment of tendon disorders using MSCs, little is known about the efficacy and safety of MSCs to treat these conditions in humans.…”
Section: Introductionmentioning
confidence: 99%
“…MSCs can not only function as seed cells of engineered myocardial tissue, bone and cartilage constructs, and important carrier cells in gene therapy, they can also repair damaged endometrium and inhibit graft vs. host responses (7). Stem cells have wide application prospects in the repair of damaged tissue (810) and may be used as a potential treatment for patients who suffer from infertility caused by intrauterine adhesions (11,12). MSC therapy is an effective treatment for myocardial necrosis of myocardial infarction, osteoporosis, bone cysts, lupus nephritis, diabetes, liver cirrhosis, liver failure, spinal cord injury and Parkinson's disease (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…[ 22 ] In a recent murine study by Liao et al., AF‐MSCs were seeded onto decellularized matrices using an infusion system based on pressurized perfusion of a cellular suspension through the fixated scaffold. [ 9 ] The generated AF‐MSCs composites displayed enhanced regenerative capacities for diaphragmatic skeletal muscle repair as opposed to dECM alone, through vascularization and functional recovery of muscular, neuronal, and tendinous structures 4 months after implantation. No hernia recurrence or clinical signs of weakness could be detected.…”
Section: Resultsmentioning
confidence: 99%